2017
DOI: 10.1108/ijmf-07-2016-0138
|View full text |Cite
|
Sign up to set email alerts
|

Institutional investors, monitoring and corporate finance policies

Abstract: Purpose The purpose of this paper is to examine the influence of institutional investors’ investment horizons (IIIH) on a wide variety of key corporate policies. Design/methodology/approach The authors perform regression analysis to a panel data set of quarterly financial statement data for US firms over the 1981-2014 using several measures of IIIH. Findings The authors argue that an increase in the presence of long-term investors contributes to more effective monitoring and information quality. This resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
(64 reference statements)
0
8
0
Order By: Relevance
“…Further, in reference to the cost of debt, there is a limited understanding on the monitoring role of institutional investors in PCFs, particularly institutional domiciles. While prior studies have found that firm outcomes do differ according to institutional investors' investment horizon (Attig et al, 2013;Cleary and Wang, 2017;Heng and Zhang, 2013) and business relationship (Abdul Wahab et al, 2008;Brickley et al, 1988), not much is known on the effect of institutional domiciles.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in reference to the cost of debt, there is a limited understanding on the monitoring role of institutional investors in PCFs, particularly institutional domiciles. While prior studies have found that firm outcomes do differ according to institutional investors' investment horizon (Attig et al, 2013;Cleary and Wang, 2017;Heng and Zhang, 2013) and business relationship (Abdul Wahab et al, 2008;Brickley et al, 1988), not much is known on the effect of institutional domiciles.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Agrawal and Mandelker (1990), Bathala et al (1994), Seetharaman et al (2001), An and Zhang (2013) and Cleary and Wang (2017) support the claim that institutional investors play an important role in monitoring the activities of management and in reducing agency problems engendered by separating corporate ownership and control.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 75%
“…Based on the above-mentioned developments, one might well notice that the large institutional investors' focus on short-term objectives leads to the strengthening of myopic behavior and managerial opportunism (Cleary and Wang, 2017). Indeed, managers are incited to meet such shareholders' expectations even if this requires resorting to pursue certain earnings management practices.…”
Section: Speculative Institutional Investors' Passivitymentioning
confidence: 99%
See 2 more Smart Citations